Safety of inactivated SARS-CoV-2 vaccines in myasthenia gravis: A survey-based study - Hong-Yan Li; Li-Yuan Shao; Min Song; Shi-Min Hu; Yao-Xian Yue; Hai-Feng Li (Frontiers in Immunology, 2022)
BackgroundVaccination remains the most effective measure to prevent SARS-CoV-2 infection and worse outcomes. However, many myasthenia gravis (MG) patients are hesitant to receive vaccine due to fear of worsening.MethodsMG patients were consecutively enrolled in two MG centers in North China. The “worsening” after vaccination was self-reported by MG patients, and severity was measured with a single simple question. The general characteristics and disease status immediately prior to the first dose were compared between the worsening and non-worsening groups. Independent factors associated with worsening were explored with multivariate regression analysis.ResultsOne hundred and seven patients were included. Eleven patients (10.3%) reported worsening after vaccination, including eight patients with mild or moderate worsening and three patients with severe worsening. Only one of them (0.9%) needed an escalation of immunosuppressive treatments. There were significant differences between the worsening and non-worsening groups in terms of Myasthenia Gravis Foundation of America classes immediately before the first dose and intervals since the last aggravation. Precipitating factors might contribute to the worsening in some patients. Logistic regression revealed that only interval since the last aggravation ≤6 months was associated with worsening after SARS-CoV-2 vaccination (P = 0.01, OR = 8.62, 95% CI: 1.93–38.46).ConclusionSARS-CoV-2 vaccines (an overwhelming majority were inactivated vaccines) were found safe in milder Chinese MG patients who finished two doses. Worsening after vaccination was more frequently seen in patients who were presumed as potentially unstable (intervals since last aggravation ≤6 months). However, mild worsening did occur in patients who were presumed to be stable. Precipitating factors should still be sought and treated for better outcome.